Market Penetration by Indian Banks: Motives and Motivators - Singh, Dilpreet; Singh, Harpreet (Indian Journal of Finance, 2016)
In the recent past, Indian banks have heavily focused on market penetration. The present study is an attempt to find the motives and motivators of the same. An empirical analysis of the views of 364 bank strategists from 21 public sector and 12 private sector Indian banks revealed that profit and growth concerns, regulatory compulsions, competitive pressures, cost considerations, social motive, and demand-side changes are motivators/motives of market penetration. The results of multiple regression analysis showed that three variables: profit and growth concerns, regulatory compulsions, and cost considerations were statistically significant in the model at the 5% significance level.